Paths of Cultural Transmission Between Syria and Ethiopia: About a Recent Book on Symbolic Interpretations - Camplani, Alberto (Aethiopica, 2021)
This contribution discusses Ralph Lee’s volume Symbolic Interpretations in Ethiopic and Early Syriac Literature, in particular his proposal about what were the channels of cultural transmission between Syriac and Ethiopic Christian literatures which could justify the consistent number of parallels found in the two poetical and liturgical traditions. Lee’s model used to explain these parallels is proved questionable, and an alternative hypothesis is offered: Ephrems’ poetry influenced later Syriac writers and liturgical traditions, which, in turn, experienced a long season of translation from Syriac to Arabic in a broad geographical area. As a consequence of this process, several streams of Ephremian tradition were transferred from the Arabic Christian literatures to the Ethiopic world after the twelfth century.